Dzyadyk's Technique for Ordinary Differential Equations Using Hermitian Interpolating Polynomials - Rizk, M.M. (Український математичний журнал, 2001)
For the case of Hermitian interpolation, we consider the approximation-iterative method introduced by Dzyadyk. We construct a practical algorithm. Розглянуто апроксимаційно-ітеративний метод В. К. Дзядика у випадку ермітової інтерполяції. Побудовано практичний алгоритм.